2017
DOI: 10.4103/0366-6999.202742
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends for ST-segment Elevation Myocardial Infarction during the Past 5 Years in Rural Areas of China's Liaoning Province

Abstract: Background:Since 2010, two versions of National Guidelines aimed at promoting the management of ST-segment elevation myocardial infarction (STEMI) have been formulated by the Chinese Society of Cardiology. However, little is known about the changes in clinical characteristics, management, and in-hospital outcomes in rural areas.Methods:In the present multicenter, cross-sectional study, participants were enrolled from rural hospitals located in Liaoning province in Northeast China, during two different periods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In this multicenter study, STEMI patients were recruited by 2 stages. As previously described elsewhere, [23] 12 secondary hospitals located in rural areas of China's Liaoning province were randomly sampled in the first stage (June 2009 to June 2010). All patients presenting with STEMI at those hospitals were consecutively enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…In this multicenter study, STEMI patients were recruited by 2 stages. As previously described elsewhere, [23] 12 secondary hospitals located in rural areas of China's Liaoning province were randomly sampled in the first stage (June 2009 to June 2010). All patients presenting with STEMI at those hospitals were consecutively enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…Early myocardial reperfusion by primary percutaneous coronary intervention (PCI) has become an important treatment strategy for patients with ST-segment elevated myocardial infarction (STEMI), which is associated with reduced infarct size, preserved cardiac function and improved clinical outcomes in these patients 1,2. However, despite effective reperfusion by PCI, a considerable proportion of patients with STEMI still have impaired cardiac function and increased cardiovascular mortality 3,4. It has been demonstrated that coronary microvascular dysfunction and obstruction, which occur in almost half of STEMI patients after primary PCI, are important causes of subsequent deterioration of cardiac function and poor prognosis in these patients 5,6.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a significant decrease in mortality associated with cardiovascular disease in developed countries over the last decade,[ 1 2 ] acute myocardial infarction (AMI) continues to be a major cause of morbidity and mortality. [ 3 4 ] ST-segment elevation myocardial infarction (STEMI) constitutes more than 80% of MI patients in China;[ 5 ] percutaneous coronary intervention (PCI) is the established acute reperfusion therapy for STEMI. [ 6 ] STEMI remains the major contributor to death in females who suffer from cardiovascular disease at an older age compared with males,[ 7 8 9 ] with females being reported to have more risk factors.…”
Section: Introductionmentioning
confidence: 99%